(untitled) (International Journal of Nursing Education, 2021)
Background of the Study: Aggression is one of the most prevalent behavioral aspects in children which cause a lot of concern in present days. Reactively aggressive children do not seek to meet goals through aggressive behavior. Instead they react negatively to perceived or actual threats and are easily irritated. Objective: The study examines the aggressive behavior among school children attending higher primary school in selected village, Mangalore. Methods: A non-experimental descriptive design was chosen to assess the aggressive behavior among children by using a Modified Overt Aggression Scale and total of 60 samples were selected using the Snowball sampling technique. Results: The findings clearly revealed that 48 subjects (80%) were having mild aggressive behavior. With regard to the association of demographic variables, religion, birth order, occupational status of parents, family income and parents opinion regarding aggressive behavior had statistically significant association with the aggressive behavior among children attending higher primary school at p<0.05 level. Conclusion: The study infers that adolescents have considerable level of aggressive behavior. It is important to indicate that aggression is a problem which continues through the adolescents and adulthood and hence it is just not a problem at that point of time.